Removal and transformation of organic matters in domestic wastewater during lab-scale chemically enhanced primary treatment and a trickling filter treatment - Zhao, Qingliang (2015)
To find a simple and economical way for treating the domestic wastewater in small counties and towns, a process combining chemically enhanced primary treatment and a trickling filter (CEPT-TF, representing the physical and biological effects) was constructed and operated in laboratory conditions. The characteristic behaviors of dissolved organic matter in raw wastewater and effluents were examined during steady-state operation. Experimental results showed that the process of CEPT and TF in series was beneficial for the removal of hydrophobic and hydrophilic organics. Specially, the hydrophobic and aromatic materials could be preferentially removed in the CEPT unit, and the hydrophilic fraction in the TF. Structural changes of the organic fractions during the operation of the different units were also characterized via spectrum analysis.